2017
DOI: 10.1371/journal.pone.0181125
|View full text |Cite
|
Sign up to set email alerts
|

High systemic IL-6 is associated with worse prognosis in patients with non-small cell lung cancer

Abstract: Characteristic cytokine patterns have been described in different cancer patients and they are related to their diagnosis, prognosis, prediction of treatment responses and survival. A panel of cytokines was evaluated in the plasma of non-small cell lung cancer (NSCLC) patients and healthy controls to investigate their profile and relationship with clinical characteristics and overall survival. The case-controlled cross-sectional study design recruited 77 patients with confirmed diagnosis of NSCLC (cases) and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 45 publications
10
86
1
1
Order By: Relevance
“…On the contrary, insulin-stimulated AKT/TBC1D4 signaling was 436 upregulated in skeletal muscle of tumor-bearing mice. This is surprising, given that tumor-bearing 437 mice displayed increased whole-body inflammation as indicated by increased spleen volume and 438 increased plasma levels of IL-6 and TNF-α, consistent with other investigations showing increased 439 IL-6 in patients with non-small cell lung cancers [49,50]. Inflammation would be expected to 440 reduce insulin signaling in muscle [51].…”
Section: Discussion 418supporting
confidence: 53%
“…On the contrary, insulin-stimulated AKT/TBC1D4 signaling was 436 upregulated in skeletal muscle of tumor-bearing mice. This is surprising, given that tumor-bearing 437 mice displayed increased whole-body inflammation as indicated by increased spleen volume and 438 increased plasma levels of IL-6 and TNF-α, consistent with other investigations showing increased 439 IL-6 in patients with non-small cell lung cancers [49,50]. Inflammation would be expected to 440 reduce insulin signaling in muscle [51].…”
Section: Discussion 418supporting
confidence: 53%
“…While other studies demonstrated the role of IL6 in promoting anti-tumor immunity through the stimulation of proliferation, survival and trafficking of T cells to lymph nodes and tumor sites, where T cells effectively shift tumor-suppressive state to responsive state to inhibit tumor growth and progression (89,90). An increased level of IL6 correlates with the poor prognosis and survival of lung cancer patients (54,60). TAM-derived IL6 plays a role in progression, invasion, angiogenesis, EMT, immune cell infiltration, and cancer stem cell (CSC) development and maintenance, through multiple unexplored molecular mechanisms (91)(92)(93).…”
Section: Cytokines Il6mentioning
confidence: 99%
“…The research and findings discussed indicate that IL‐6 overexpression is closely related to tumor activities, such as biogenesis, development, metastasis, and invasion. Related research has also indicated a significant negative correlation between the prognosis of NSCLC patients and IL‐6 concentrations in their serum . Therefore, inhibiting IL‐6 may be effective for impeding tumor development.…”
Section: Il‐6‐related Progress In Tumor Treatments In Internal Medicinementioning
confidence: 99%
“…Related research has also indicated a significant negative correlation between the prognosis of NSCLC patients and IL-6 concentrations in their serum. 34 Therefore, inhibiting IL-6 may be effective for impeding tumor development.…”
Section: Application Of Il-6 Inhibitor To Lung Cancer Treatmentsmentioning
confidence: 99%